Model hubungan aktor pemangku kepentingan dalam pengembangan potensi pariwisata Kedung Ombo - Nafiah Ariyani; Akhmad Fauzi; Farhat Umar (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
The success of developing tourist destinations requires an analysis of actors’ characteristics regarding the relationships between actors, actors’ attitudes towards development goals, and the probable alliances and conflicts. This study aims to identify actors’ typologies based on the strengths and relationships between actors and actors’ attitudes towards developing the Kedung Ombo tourist destination. This study uses a qualitative-quantitative research paradigm. Data collection relies on in-depth interviews, focus group discussions, and workshops. Data are then analyzed using the Mactor method (Matrix of Alliances and Conflicts Tactics, Objectives, and Recommendations) to identify stakeholders’ strengths, relationships, and alliance patterns. The results show that the Pemalijuana River Basin Center, Perum Perhutani, and the Regional Development Planning Agency are the dominant actors. Meanwhile, the Youth, Sports, and Tourism Regional Office, higher education institutions, village governments, communities, and business actors are relay actors, and Karang Taruna is the dominated actor. Most stakeholders converge in supporting the achievement of the strategic goals. These findings are the basis for developing a collaborative pattern between all stakeholders needed to sustain Kedung Ombo’s tourism potentials.